Ultrathin Injectable Sensors of Temperature, Thermal Conductivity, and Heat Capacity for Cardiac Ablation Monitoring. Issue 3 (9th December 2015) - Koh, Ahyeon; Gutbrod, Sarah R.; Meyers, Jason D.; Lu, Chaofeng; Webb, Richard Chad; Shin, Gunchul; Li, Yuhang; Kang, Seung‐Kyun; Huang, Yonggang; Efimov, Igor R.; Rogers, John A.
Abstract : Knowledge of the distributions of temperature in cardiac tissue during and after ablation is important in advancing a basic understanding of this process, and for improving its efficacy in treating arrhythmias. Technologies that enable real‐time temperature detection and thermal characterization in the transmural direction can help to predict the depths and sizes of lesion that form. Herein, materials and designs for an injectable device platform that supports precision sensors of temperature and thermal transport properties distributed along the length of an ultrathin and flexible needle‐type polymer substrate are introduced. The resulting system can insert into the myocardial tissue, in a minimally invasive manner, to monitor both radiofrequency ablation and cryoablation, in a manner that has no measurable effects on the natural mechanical motions of the heart. The measurement results exhibit excellent agreement with thermal simulations, thereby providing improved insights into lesion transmurality. Abstract : Ultrathin flexible and injectable sensors enable detection of temperature, thermal conductivity, and heat capacity as a function of depth into myocardial tissue during cardiac ablation therapy. This transverse chronothermographic measurement allows detailed characterization of the lesion transmurality.